The Fatigue of the Shari‘a: By Ahmad Atif Ahmad (New York: Palgrave Macmillan, 2012. 208 pages.) (American Journal of Islam and Society, 2015)
In this challenging and thought-provoking monograph, Ahmad Atif Ahmaddraws on the issue of futūr al-Sharī‘a (the end of access to divine guidancedue to the absence of qualified jurists) to explore how early Muslim scholarsdebated its possible loss. Basing himself upon the analysis of medieval Sunnilegal and theological texts, the author divides his monograph into four parts:Part I, “Foundations,” chapters 1-3; Part II, “Jurists and Nonjurists,” chapters4-6; Part III, “Modernity and Its Questions,” chapters 7-8; and Part IV, “BeyondModernity,” chapters 9-10.Ahmad situates his project as a commentary on the debate over the destinyof religious teachings “from the point of view of Muslim jurist-theologiansand those who engaged the intellectual production of these jurists and theologians”(p. 1). He pursues his central goal, to explore “the destiny and currentstatus of God’s guidance from a Muslim perspective” (p. 2), by explainingthat medieval Muslim theologians and jurists defined the Shari‘a’s survivalin terms of the availability of scholarly “knowledge” about it (p. 2). Utilizingthese medieval debates to offer important insights into similar contemporarydebates, he insists that empirical research will continue to refute the “death ofthe sharī‘a” thesis.In the Introduction, Ahmad poses a question that goes to the heart of thisdebate: Could God’s guidance, available to previous generations as religioushistories tell us, somehow become inaccessible at some point? His premise isthat the “fatigue of the sharī‘a” has been a subject of continuous debatethroughout the Islamic tradition and thus cannot be considered a “recent” or“modern” phenomenon. He closely evaluates two kinds of debates: (1) thosein the Islamic tradition about the end of access to futūr al-Sharī‘a and (2) thosein modern western scholarship in the discipline of Islamic legal studies aboutthe Shari‘a’s death.One of the important issues in this book is Ahmad’s discussion of thissupposed “fatigue” in relation to other intertwined inquiries about the natureof ijtihād (independent reasoning), God’s guidance and justice, and the availabilityof His guidance today (p. 15). This suggests to the reader that the claimsmade about this fatigue can be answered only after addressing auxiliary, yetfundamental, concerns about the Shari‘a in Muslim societies. Ahmad furthercomplicates the question of its death by pointing out the medieval relationshipbetween legal and theological reflections on this question. He alerts readersto the problem of defining “sharī‘a” and “fatigue of the sharī‘a” and observes ...